Prevalence of Dyslipidaemia and Pre-Diabetes Among Women with Polycystic Ovary Syndrome (PCOS): Do We Overestimate Cardiovascular Risk? - Lewandowski, Krzysztof C.; Płusajska, Justyna; Horzelski, Wojciech; Lewiński, Andrzej (Hormone and Metabolic Research, 2019)
PCOS is widely accepted as associated with an increased cardiovascular risk, however, without convincing evidence of an increased cardiovascular mortality. We assessed prevalence of obesity, glucose intolerance, and dyslipidaemia in 490 women with PCOS, aged 24.75±8.05 years, diagnosed according to the Rotterdam consensus criteria. Fifty-two percent of women had BMI<26 kg/m2, 81.8% had total cholesterol<200 mg/dl, 82.8% had LDL cholesterol<130 mg/dl (48.3%<100 mg/dl), 81.4% had triglycerides<150 mg/dl, 96.08% had fasting glucose<100 mg/dl, 90.3% had glucose<140 mg/dl at 120′ of OGTT. The most frequent abnormality was low HDL cholesterol, as only 33.9% had LDL>60 mg/dl. Combination of several risk factors related to dyslipidaemia was, however, relatively rare, for example, a combination of raised total cholesterol and LDL cholesterol was present only in 2.9% of subjects. An increase in BMI, total cholesterol, LDL-cholesterol, and glucose concentrations at 120′ of OGTT was more pronounced in women, who had raised concentrations of at least two androgens (n=172, 35.1%), yet there was no increase in insulin resistance parameters, that is, HOMA-IR, QUICKI, McAuley, or Belfiore index. Contrary to common belief, over 50% of women with PCOS have normal body weight, and with exception of lower HDL cholesterol, most have no significant dyslipidaemia or glucose intolerance. Women with normal or borderline abnormal androgens, who form the majority of PCOS subjects, seem to have more healthy metabolic profile. This might be one of the reasons for the absence of evidence of an increased CV mortality in women with PCOS.
Keywords: androgens; insulin resistance; glucose intolerance dyslipidaemia; PCOS